Implementasi Nilai-Nilai Pancasila dengan Pendekatan Contextual Teaching Learning untuk Menumbuhkan Karakter Mahasiswa - Yeni Asmara; Abu Bakar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to find out and describe the implementation of Pancasila values ​​with the Contextual Teaching Learning approach as an effort to grow the character of STKIP PGRI Lubuklinggau students. This research is a qualitative research with a descriptive approach. The subjects in this study were the fourth semester students of the PJKR Study Program. Data collection techniques using questionnaires and observations. Data analysis in this research was in the form of descriptive analysis. The results of the study, the careful character as the implementation of Pancasila values ​​in students through the CTL (Contextual Teaching Learning) approach is good, this can be seen from the criteria of character implementation in the range of 61-80%, the careful character has been implemented 70.31%. For creative characters is good enough, seen from the implementation criteria in the range of 41% -60%. The creative character has been implemented at 62.5%. Meanwhile the character of hard work is good, judging by the implementation criteria in the range of 61% -80%. The character of hard work has been implemented 62.5%. Then the character of curiosity in the range of 61% -80% is categorized as good, from the observation results have been implemented 70.31% by students. In conclusion, the implementation of Pancasila values ​​in STKIP PGRI students using the CTL (Contextual Teaching Learning) approach to grow student character has been well seen from various indicators that exist on various characters. Keywords: Contextual Teaching Learning, Character, Pancasila Values